Endoscopic retrograde cholangiopancreatography in children: Retrospective series with a long-term follow-up and literature review - Yavor Asenov,; Melih Akın,; Serdar Cantez,; Feryal Gün Soysal,; Yaman Tekant, (Turkish Journal of Gastroenterology, 2019)
Background/Aims: To investigate the safety and long-term results of endoscopic retrograde cholangiopancreatography (ERCP) in children with a literature review. Materials and Methods: All patients within the age range of 6-17 years who underwent ERCP between 1994 and 2014 at our institution were retrospectively evaluated. Result: Twenty-four patients with a median age of 15 years underwent ERCP. Cannulation of the papilla was achieved in all patients (100%) without the use of needle-knife papillotomy. Before 1999, ERCP was used as a diagnostic method only in 7 patients (29%). In 17 (71%) patients, the procedure was used for therapeutic purposes. The indications were choledocholithiasis (10 cases, 42%), postoperative complications (5 patients, 21%), and recurrent pancreatitis (2 cases, 8%). In 2 patients (8%), the therapeutic effect was not achieved, thus requiring subsequent operations. There were no major complications. Mild pancreatitis occurred in only 1 patient (4%). Long-term follow-up information was obtained in 16 (67%) patients (median, 18 years; range, 3.5-22.5 years), and no long-term complications were detected. Conclusion: Endoscopic retrograde cholangiopancreatography is a valuable tool in the diagnosis and treatment of pancreatobiliary disorders in the pediatric population. Large-scale studies are required to create evidence-based guidelines specific to children. Cite this article as: Asenov Y, Akın M, Cantez S, Gün Soysal F, Tekant Y. Endoscopic retrograde cholangiopancreatography in children: Retrospective series with a long-term follow-up and literature review. Turk J Gastroenterol 2019; 30(2): 192-7.